The New Leadership Paradigm in Digital Health and Its Relations to Hospital Services (Jurnal Ilmu Kesehatan Masyarakat, 2021)
The current and future of the healthcare system will face various problems, ranging from digitizing the health system, digital transformation and disruption of the health world or the problem of digital application during the Covid-19 pandemic in Health 4.0 and Community 5.0 and its leadership. The objective of the study is to explore digital information and the role of leadership in healthcare services in the future. This research is a narrative literature review and searched relevant articles from ProQuest and PubMed. Digital health is transforming healthcare delivery around the world to meet the evolving challenges of an aging population with a variety of chronic conditions. Digital transformation and disruptive innovation illustrate a comprehensive reorientation of the industry, including its business model due to the advent of digital technology in the form of digitizing products, services, and processes. Digital health products can be in the form of electronic health (eHealth), cellular health (mHealth), health information technology, teleconsultation (telehealth/telemedicine). All these digital products, if they cannot be applied now and in the future, will cause digital disruption in traditional healthcare services in hospitals. The current world of health also has an impact because of the COVID-19 pandemic, where this situation is a race for Health 4.0 and Society 5.0 (super smart people). Where Health 4.0 will relax and reflect digital health and implement it in Society 5.0. The leadership strategies that can be selected are systems thinking, contextual intelligence, and metacognitive strategies.